FAKTOR FUNDAMENTAL, KEBIJAKAN DEVIDEN DAN HARGA SAHAM SEKTOR MANUFAKTUR DI BURSA EFEK INDONESIA - Ni Made Riani (Jurnal Manajemen dan Bisnis, 2013)
Company’s main objective is to increase corporate stock price. High stock pricecompanies that can increase the prosperity for our shareholders, shareholders will investtheir capital to the company. Investors have the primary purpose of the funds invested intothe company to seek revenue (return) capital gain or dividend. To assess the performance ofa company in generating profits expected, investors can see from the side of its fundamentalaspect, the better the fundamental performance of a company has, the higher the stock priceof the company. This study aims to determine the effect of the fundamental factor of liquidity,leverage, profitability and dividend policy, against firm stock price at a manufacturingcompany that go public on the Indonesia Stock Exchange.The population in the study is a manufacturing company that distribute dividends inthe Indonesia Stock Exchange 2006 until 2009 with 67 companies. The samples were selectedbased on purposive sampling that pays dividends resprectively from 2006 until 2009 with 28sample firms. The method of analysis used is the technique of path analysis.The results of this study are 1) Liquidity significant positive effect on DividendPolicy; 2) Leverage a significant negative effect on Dividend Policy; 3) The profitability of asignificant positive effect on Dividend Policy; 4) Liquidity significant positive effect on thefirm stock price; 5) Profitability significant positive effect on the firm stock price, and 6)Dividend Policies significant positive effect on the firm stock price. Dividend policy can alsobe used as information for issuers and companies in the capital market to firm stock pricebecause the results observed in this study dividend policy can provide a positive signal. If thedividend policy increase the stock price of the company will also increase.Keywords : liquidity, leverage, profitability, dividend policy and firm stock price.